2009
DOI: 10.1371/journal.pgen.1000696
|View full text |Cite
|
Sign up to set email alerts
|

High-Density SNP Screening of the Major Histocompatibility Complex in Systemic Lupus Erythematosus Demonstrates Strong Evidence for Independent Susceptibility Regions

Abstract: A substantial genetic contribution to systemic lupus erythematosus (SLE) risk is conferred by major histocompatibility complex (MHC) gene(s) on chromosome 6p21. Previous studies in SLE have lacked statistical power and genetic resolution to fully define MHC influences. We characterized 1,610 Caucasian SLE cases and 1,470 parents for 1,974 MHC SNPs, the highly polymorphic HLA-DRB1 locus, and a panel of ancestry informative markers. Single-marker analyses revealed strong signals for SNPs within several MHC regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
105
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 44 publications
9
105
2
2
Order By: Relevance
“…We observed some suggestive associations near HLA-B and -C and non-HLA genes (PZ1.37 Â 10 À 6 ) after conditioning on all HLA-DRB1 signals. This observation could be consistent with other fine-mapping studies that showed evidence of multiple independent associations in the MHC region [6][7][8][9] . Therefore, in the future, it is important to expand the same finemapping study on HLA alleles, HLA amino acids and SNPs with a larger sample size and multiple ancestral samples.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed some suggestive associations near HLA-B and -C and non-HLA genes (PZ1.37 Â 10 À 6 ) after conditioning on all HLA-DRB1 signals. This observation could be consistent with other fine-mapping studies that showed evidence of multiple independent associations in the MHC region [6][7][8][9] . Therefore, in the future, it is important to expand the same finemapping study on HLA alleles, HLA amino acids and SNPs with a larger sample size and multiple ancestral samples.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have attempted to dissect the SLE association within the extended MHC locus characterized by a high degree of linkage disequilibrium (LD) and genetic diversity [6][7][8][9][10] . Multiple HLA alleles and non-HLA variants in MHC locus have been suggested to have independent SLE-risk effects, as demonstrated by stepwise conditional analysis or HLA allele-allele haplotype analysis to control for the LD effect [6][7][8][9] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the same reason, we did not include the multiple SNPs in the HLA region, which were shown to be independently associated with SLE in other populations. 38 Therefore, our current model represents only a proportion of the whole genetic contribution to SLE, and should be improved in the future by incorporating additional susceptibility genes when their association was replicated in the Japanese.…”
Section: Association Between Cumulative Risk Allele Number and Clinicmentioning
confidence: 99%
“…The defect in these genes is although rare but susceptibility in most patients arises from a combination of normal variation in different genes. High-density SNP screening of the major histocompatibility complex in SLE showed strong evidence for independent susceptibility regions including HLADR2, HLADR3, and HLA-DRB1 [24]. There are other types of genes that can regulate the immune system, are also implicated in SLE.…”
Section: Genetic Factorsmentioning
confidence: 99%